TAWARAN PEMIKIRAN ‘KIRI ISLAM’ HASSAN HANAFI DAN RELEVANSINYA DALAM PENDEKATAN METODE DAKWAH DI SAMBAS - Dulhadi, Dulhadi (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2020)
Hassan Hanafi is one of the Islamic thinkers who has developed a multidisciplinary method of thinking, at least combining Islamic scientific traditions and Western methods which emphasize methodological aspects, his popular thought is the conception of the Islamic Left which offers the idea of ​​renewal that includes four central ideas: revitalization of classical Islamic treasures, answer the challenges of civilization, seek revolutionary elements in religion and create Islamic national integrity. These four ideas are then relevant to the author by looking at the methods of preaching, especially in Sambas. The aspect that can be seen in this thinking is the ability to see the achievements of the previous ulama/dai who have been able to preach Islam so that it becomes the majority religion in the Sambas community. The ability to integrate Islamic teachings and aspects that smell local in this term is called local wisdom. In expressing this idea, the writer uses an intellectual history approach that focuses on the existence of Zeitgeist (the soul of the times) of the past Sambas community.